2013
DOI: 10.1186/1479-5876-11-58
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics and prognostic analysis of Lauren classification in gastric adenocarcinoma in China

Abstract: BackgroundAccording to the Lauren classification, gastric adenocarcinomas are divided into diffuse and intestinal types. The causative attribution explaining the dismal prognosis of diffuse-type remains unknown.MethodsWe examined the archive of 1000 patients with gastric adenocarcinomas who received radical gastrectomy in our center and assessed the effect of the Lauren classification on survival in a multivariate approach. Moreover we compared the variation of clinical features between the diffuse-type and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
114
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 148 publications
(135 citation statements)
references
References 20 publications
16
114
1
4
Order By: Relevance
“…The difference in tumor extension between intestinal and diffuse-type carcinoma is of clinical significance in the selection of a suitable treatment strategy (14,15). In the present study, the younger age (P=0.023), higher T (P=0.020), N (P=0.032) and TNM stage (P=0.039) of patients with diffuse-type GC indicated that diffuse-type was more invasive than intestinal-type GC, which may contribute to the poorer prognosis of patients with diffuse-type carcinoma (30). An improved understanding of the underlying pathogenesis and molecular events of the two histological subtypes may facilitate the development of novel diagnostic, therapeutic and preventive strategies for GC.…”
Section: Discussionmentioning
confidence: 52%
“…The difference in tumor extension between intestinal and diffuse-type carcinoma is of clinical significance in the selection of a suitable treatment strategy (14,15). In the present study, the younger age (P=0.023), higher T (P=0.020), N (P=0.032) and TNM stage (P=0.039) of patients with diffuse-type GC indicated that diffuse-type was more invasive than intestinal-type GC, which may contribute to the poorer prognosis of patients with diffuse-type carcinoma (30). An improved understanding of the underlying pathogenesis and molecular events of the two histological subtypes may facilitate the development of novel diagnostic, therapeutic and preventive strategies for GC.…”
Section: Discussionmentioning
confidence: 52%
“…4,10,14,19 Rannsóknir eru þó ekki allar alveg samhljóma og hafa sumar sýnt fram á faekkun í báðum hópunum. 20,21 Líkt og aðrir hafa sýnt fram á, þar með talið Laurén sjálfur, voru þeir sem greindust með dreifkrabbamein í okkar rannsókn yngri 10,22,23 og kynjahlutfallið í hópi dreifkrabbameina jafnara. 22,23 Fyrri rannsóknir hafa þegar sýnt verri lifun sjúklinga með dreifkrabbamein en þó ekki allar eftir að leiðrétt hefur verið fyrir öðrum samverkandi þáttum.…”
Section: Umraeðurunclassified
“…20,21 Líkt og aðrir hafa sýnt fram á, þar með talið Laurén sjálfur, voru þeir sem greindust með dreifkrabbamein í okkar rannsókn yngri 10,22,23 og kynjahlutfallið í hópi dreifkrabbameina jafnara. 22,23 Fyrri rannsóknir hafa þegar sýnt verri lifun sjúklinga með dreifkrabbamein en þó ekki allar eftir að leiðrétt hefur verið fyrir öðrum samverkandi þáttum. 24,25 Rannsókn okkar leiddi hins vegar í ljós marktaekan mun á lifun útfrá Laurén-flokkun eftir leiðréttingu fyrir ýmsum samverkandi þáttum, þar með talið stigi og niður-stöðu aðgerðar.…”
Section: Umraeðurunclassified
See 1 more Smart Citation
“…Histologically, GCs are highly heterogeneous tumours in terms of structural or cytological features. Throughout the last fifty years, the histologic classification of GC has continued mostly with reference to Lauren design, in which diffuse and intestinal carcinoma are the two main histologic sub-groups in addition to uncommon variants such as 'indeterminate type' (Hu et al, 2012;Fontana et al, 2003;Qiu et al, 2013).…”
Section: Goseki Grade and Tumour Locationmentioning
confidence: 99%